DRUG UTILIZATION PATTERN IN DENTAL OUTPATIENT DEPARTMENT OF A RURAL TERTIARY CARE HOSPITAL - Dr. CHINCHOLKAR APARNA,; Dr. JAPTIWALE SUBHASH, (International Journal of Pharma and Bio Sciences, 2015)
The present study was undertaken to know the trends of drug prescribing in dental outpatient department (OPD) of a rural tertiary care hospital. A prospective prescription audit was conducted for a period of 3 months from February 2015 to April 2015 at dental OPD and data was analyzed using WHO indicators/guidelines. The total number of prescriptions analyzed was 250. Average number of medicines per prescription was 2.8. Of the total medications prescribed, 32% each were antimicrobial agents and analgesics-antiinflammatory agents, and the percentage of antiulcer drugs was 26.1%. Most commonly prescribed antimicrobial agent (87.5%) was a fixed dose combination of amoxicillin and cloxacillin. Most commonly prescribed analgesic-anti inflammatory agent (57.01%) was a fixed dose combination of ibuprofen and paracetamol. Some other medications included preparations of multivitamins and oropharyngeal mouthwashes and pastes. Antimicrobial agents and analgesic-antiinflammatory agents were prescribed as fixed dose combinations to a majority of patients. The high incidence of their use as fixed dose combinations needs to be addressed by a feedback to the prescribers. The prescribers need to be sensitized regarding rational prescribing as well as the importance of choosing drugs from essential drug list.